An Exploration of English Teachers' Instructional Communities of Practice: A Multiple Case Study - Arabis, Jenny P (Yayasan Nurul Yakin Bunga Tanjung, 2025)
This multiple case study aimed to explore language teachers’ experiences with a focus on their strategies and challenges in delivering distance learning and transitioning to limited face-to-face classes. The study was conducted with six English language teachers from the College of Education at Jose Rizal Memorial State University in Zamboanga del Norte, Philippines. The data collection process involved semi-structured interviews to gather in-depth narratives of participants’ experiences. Thematic analysis was used, a method that involves systematically identifying, coding, and categorizing patterns in participants’ narratives to uncover recurring themes and insights. Key findings revealed that teachers leveraged flexible scheduling to increase productivity and develop innovative teaching methods. Despite these efforts, lack of internet access among students emerged as a significant challenge, requiring teachers to provide additional support outside of regular hours, often through text and messaging platforms. Further challenges included the late start of the school year and inadequate classroom space, which required make-up sessions and additional adjustments to meet academic requirements. Based on these findings, participants recommended further professional development opportunities, financial assistance, material support, and a reassessment of teaching modalities to improve learning effectiveness in similar challenging contexts.